Simultaneous integrated boost plan comparison of volumetric‐modulated arc therapy and sliding window intensity‐modulated radiotherapy for whole pelvis irradiation of locally advanced prostate cancer. (8th July 2013) - Riou, Olivier; de la Mothe, Pauline Regnault; Azria, David; Aillères, Norbert; Dubois, Jean‐Bernard; Fenoglietto, Pascal
Abstract : Concurrent radiotherapy to the pelvis plus a prostate boost with long‐term androgen deprivation is a standard of care for locally advanced prostate cancer. IMRT has the ability to deliver highly conformal dose to the target while lowering irradiation of critical organs around the prostate. Volumetric‐modulated arc therapy is able to reduce treatment time, but its impact on organ sparing is still controversial when compared to static gantry IMRT. We compared the two techniques in simultaneous integrated boost plans. Ten patients with locally advanced prostate cancer were included. The planning target volume (PTV) 1 was defined as the pelvic lymph nodes, the prostate, and the seminal vesicles plus setup margins. The PTV2 consisted of the prostate with setup margins. The prescribed doses to PTV1 and PTV2 were 54 Gy in 37 fractions and 74 Gy in 37 fractions, respectively. We compared simultaneous integrated boost plans by means of either a seven coplanar static split fields IMRT, or a one‐arc (RA1) and a two‐arc (RA2) RapidArc planning. All three techniques allowed acceptable homogeneity and PTV coverage. Static IMRT enabled a better homogeneity for PTV2 than RapidArc techniques. Sliding window IMRT and VMAT permitted to maintain doses to OAR within acceptable levels with a low risk of side effects for each organ. VMAT plans resulted in a clinically and statistically significant reduction in doses to bladder (mean dose IMRT: 50.1 ± 4.6 Gy vs. mean dose RA2: 47.1 ± 3.9 Gy, p = 0.037 ), rectum (mean dose IMRT: 44 ± 4.5 vs. mean dose RA 2 : 41.6 ± 5.5 Gy, p = 0.006 ), and small bowel ( V 30 IMRT : 76.47 ± 14.91 % vs. V 30 RA 2 : 47.49 ± 16.91 %, p = 0.002 ). Doses to femoral heads were higher with VMAT but within accepted constraints. Our findings suggest that simultaneous integrated boost plans using VMAT and sliding window IMRT allow good OAR sparing while maintaining PTV coverage within acceptable levels. PACS number: 87.53.Jw